2015
DOI: 10.1093/jb/mvv098
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular accumulation of indium ions released from nanoparticles induces oxidative stress, proinflammatory response and DNA damage

Abstract: Due to the widespread use of indium tin oxide (ITO), it is important to investigate its effect on human health. In this study, we evaluated the cellular effects of ITO nanoparticles (NPs), indium chloride (InCl3) and tin chloride (SnCl3) using human lung epithelial A549 cells. Transmission electron microscopy and inductively coupled plasma mass spectrometry were employed to study cellular ITO NP uptake. Interestingly, greater uptake of ITO NPs was observed, as compared with soluble salts. ITO NP species releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 57 publications
0
27
1
3
Order By: Relevance
“…In line with our results, several studies have shown that ZnO NPs or other types of NPs induce DNA damage in a variety of cell types. [50][51][52][53][54][55][56][57][58][59][60] In vivo exposure to ZnO NPs alters the structure of seminiferous tubules and spermatozoa morphologies…”
Section: Zno Nps Induce Nuclear Dna Leakage and Breakagementioning
confidence: 99%
“…In line with our results, several studies have shown that ZnO NPs or other types of NPs induce DNA damage in a variety of cell types. [50][51][52][53][54][55][56][57][58][59][60] In vivo exposure to ZnO NPs alters the structure of seminiferous tubules and spermatozoa morphologies…”
Section: Zno Nps Induce Nuclear Dna Leakage and Breakagementioning
confidence: 99%
“…Cellular indium uptake was much higher with sample B (≈750 pg/cell at 215 g/ml; concentration per cell estimated from a graph) than with sample A (≈150 pg/cell at 790 g/ml) (Tabei et al, 2016).…”
Section: In Vitro Experimentsmentioning
confidence: 78%
“…Therefore, the validity and reliability of test results indicating a potential for genotoxic/DNA damaging effects is difficult to assess. There are indications that the effects might be secondary, most likely as a result of ROS induction (Akyıl et al, 2015;Badding et al, 2014;Cigerci et al, 2015;Lison et al, 2009;Tabei et al, 2015Tabei et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, environmental pollution generated during indium refinery and the toxicity of indium and indium compounds to the human body have been confirmed. [8][9][10][11] Thus, development of alternative materials has been sought after. Alternative non-ITO-based transparent conductive films for application in optoelectronic devices require high conductivity and transmittance, and also be adaptable to economic and large-scale processing.…”
Section: Introductionmentioning
confidence: 99%